PENGARUH PENYETELAN KATUP PADA ENGINE 4K 4 SILINDER 1300CC TIPE OHV TERHADAP EMISI GAS BUANG - Lestari, Dwi Mardika; Ahmad Rizal Fauzi (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2021)
Indonesia is a country that has a lot of users of motorized vehicles, this is because the level of consumer need to have a motorized vehicle is very high. Cars are one of the favorite vehicles for Indonesian citizens. Because cars provide more comfort and security and now many cars are becoming luxury goods. So many people are turning to cars as their everyday vehicles. Many people want to own a car but at a cost that is not too high, namely by buying a used car. This is where used cars usually have various problems, especially in the engine and exhaust emissions that are not up to standard, therefore it is necessary to repair the car engine. In this study contains about Toyota Kijang 4K valve adjustment variations which have engine problems. To study this study there are two methods used, namely the first is the primary method obtained from direct practice and observation. The second is the secondary method, namely the method taken from internal data and external data. This research data collection resulted from variations in the valve gap ex 0.30mm valve in 0.15mm, valve ex 0.30mm valve in 0.20mm and valve ex 0.30mm valve in 0.25 at engine speed of 1000 rpm, 1500 rpm, rpm 2000, 3000 rpm, and 3500 rpm. The conclusion from the results of this study is that there is a significant effect of valve adjustment on exhaust gas emissions on a 1300cc 4k 4 cylinder 1300cc stand engine OHV type.